EVALUATION OF LEPTOSPIROSIS CONTROL MANAGEMENT BASED ON ONE HEALTH IN BOYOLALI DISTRICT - Vivin Fitriana; Riris Andono Ahmad; Hanevi Djasri (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Evaluation of leptospirosis control management based on one health in Boyolali DistrictPurpose: The study aims to evaluate the control of leptospirosis in Boyolali Regency. Method: This study was a descriptive observational. Samples were conducted with purposive sampling techniques for Boyolali District Health Office, Boyolali District Animal Husbandry Office, Boyolali District Agricultural Service, and 9 health centers with findings of leptospirosis cases in 2017-2018. Variables that evaluated included inputs, planning, implementation, output. Data were collected through Observational and interviews. Results: Seventy percent of health workers have received training. Rapid diagnosis tests (RDTs) are not available at the primary health care but available in the Health Office. Data collection is reported passively. Examination of leptospirosis cases in livestock if there are findings in humans. However, the main reservoir (rat) was not inspected by the Agriculture Office. Every case that found was reported to the Boyolali District Health Office and received treatment.Conclusion: Leptospirosis control in Boyolali Regency has not successful. It was depicted by cases of death a year after the adoption of the one health concept. Improving both quality of human resources on a regular basis and increasing collaboration between various sectors such as community leaders, religious leaders, the Livestock Service Office, the Agriculture Service, and other relevant agencies were needed.